Antagonistic Effect of Acetates in C–N Bond Formation with In Situ Generated Diazonium Salts: A Combined Theoretical and Experimental Study. Issue 35 (18th November 2016) - Fabre, Indira; Perego, Luca Alessandro; Bergès, Julien; Ciofini, Ilaria; Grimaud, Laurence; Taillefer, Marc
Abstract : The mechanism of the copper‐catalyzed arylation of nitrogen heterocycles using anilines via diazonium salts has been studied by combining DFT and experimental data. A Cu I /Cu III redox mechanism is proposed. Our study has revealed the multiple roles of the acid/base couple AcOH/AcO – . An in situ formed triazene species maintains a low concentration of diazonium salts in the reaction medium, which ensures limited formation of decomposition products. The results of DFT calculations have explained the lower reactivity of imidazole nucleophiles as compared with pyrazole in the arylation reaction. Abstract : A mechanistic study of the Cu‐catalyzed arylation of nitrogen heterocycles using anilines via diazonium salts is described. The formation of a triazene species, which acts as a dormant safe diazonium reservoir, and a Cu I /Cu III redox mechanism are proposed.